2021
DOI: 10.1007/s12119-021-09835-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Managing Gender Identity Variance in Minors: A Qualitative Research on the Parental Role in Italy

Abstract: Identities that differ from what is expected of each gender challenge the crystallised binary form of social organisation. Furthermore, having a gender-variant child is an experience that confronts parents with something unknown to them that questions most of their assumptions. In the Italian context, there is a lack of awareness about the population of transgender and gender-variant minors, and what their or their families’ needs are. In the present study, we interviewed the parents of gender-variant minors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
0
9
0
6
Order By: Relevance
“…The articles were published in 2009 (3.5%) [ 17 ], 2011 (3.5%) [ 18 ], 2013 (3.5%) [ 19 ], 2014 (7.1%) [ 20 , 21 ], 2015 (3.5%) [ 22 ], 2016 (7.1%) [ 23 , 24 ], 2018 (7.1%) [ 25 , 26 ], 2019 (17.8%) [ 27 , 28 , 29 , 30 , 31 ], 2020 (17.8%) [ 32 , 33 , 34 , 35 , 36 ], and 2021 (28.5%) [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. All articles (100%) were published in English, of which 17 (60.7%) [ 17 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 32 , 33 , 34 , 35 , 37 , 40 , 44 ] originated in America, 3 (32.1%) [ 20 , 30 , 31 , 35 , 36 , 37 , 38 , 39 , 41 , ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The articles were published in 2009 (3.5%) [ 17 ], 2011 (3.5%) [ 18 ], 2013 (3.5%) [ 19 ], 2014 (7.1%) [ 20 , 21 ], 2015 (3.5%) [ 22 ], 2016 (7.1%) [ 23 , 24 ], 2018 (7.1%) [ 25 , 26 ], 2019 (17.8%) [ 27 , 28 , 29 , 30 , 31 ], 2020 (17.8%) [ 32 , 33 , 34 , 35 , 36 ], and 2021 (28.5%) [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. All articles (100%) were published in English, of which 17 (60.7%) [ 17 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 32 , 33 , 34 , 35 , 37 , 40 , 44 ] originated in America, 3 (32.1%) [ 20 , 30 , 31 , 35 , 36 , 37 , 38 , 39 , 41 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The methodological quality of the articles included in the final sample of this review was assessed and they all showed congruence in the following aspects: philosophical perspective and research methodology; research methodology and research question or objectives; research methodology and data collection methods; participants and their voices adequately represented; compliance with ethical issues and conclusions of data analysis or interpretation [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations